PRINTED NARRATIVES OF UNREST: A STUDY OF RAILWAY STRIKES IN COLONIAL BENGAL UNTIL 1911 - Sarkar, Laboni (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The labour movement, especially the Railway working class movement in Bengal has a rich history. Prior to the significant "May Day" event in America in May 1886, a movement was initiated by 1200 workers at Howrah Railway Station in Colonial Bengal in May 1862, advocating for an eight-hour workday. This marked the commencement of strikes for the rights of railway workers in Bengal, precipitating a series of revolutionary protests until the annulment of the Partition of Bengal. Economic catastrophe, humiliation, negligence, discrimination, poor working conditions, low wages, etc. forced the working classes to organise all those movements which have been reflected in contemporary literary traditions. This paper is to deal with the strikes organised by the railway workers of colonial Bengal for their rights and how these labor movements have been reflected in contemporary Bengali literary traditions, especially in newspapers at that time.